MENGURAI KECANTIKAN BAHASA AL-QUR'AN: ANALISIS MENDALAM TERHADAP MAJAZ MURSAL ALAQAH JUZ’IYAH. - -, Murdiono90; Taufiq, Hadi Nur (Program Studi Bahasa dan Sastra Arab STAIN Majene, 2024)
This research aims to analyze the use of Majaz Mursal Alaqah Juz'iyyah in the Quran through the approach of Quranic Balaghah Studies. Qualitative methods are employed to explore and understand the meaning of Majaz Mursal in the context of Quranic Balaghah. The research population consists of Quranic verses containing Majaz Mursal Alaqah Juz'iyyah, with samples selected based on specific criteria. The results indicate that Majaz Mursal Alaqah Juz'iyyah is wisely utilized in the Quran, opening new dimensions of understanding divine messages. For example, in Surah Al-Lahab, the use of the term